Formation of inner-shell autoionizing CO+ states below the CO2+ threshold - Osipov, T.; Weber, Th.; Rescigno, T. N.; Lee, S. Y.; Orel, A. E.; Schöffler, M.; Sturm, F. P.; Schössler, S.; Lenz, U.; Havermeier, T.; Kühnel, M.; Jahnke, T.; et al. (My University, 2010)
We report a kinematically complete experiment on the production of CO+ autoionizing states following photoionization of carbon monoxide below its vertical double-ionization threshold. Momentum imaging spectroscopy is used to measure the energies and body-frame angular distributions of both photo- and autoionization electrons, as well as the kinetic energy release (KER) of the atomic ions. These data, in combination with ab initio theoretical calculations, provide insight into the nature of the cation states produced and their subsequent dissociation into autoionizing atomic (O∗) fragments.